2006
DOI: 10.2337/db06-0577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex and Hormone Replacement Therapy Use on the Prevalence of Isolated Impaired Fasting Glucose and Isolated Impaired Glucose Tolerance in Subjects With a Family History of Type 2 Diabetes

Abstract: Impaired fasting glucose (IFG) is more prevalent in men and impaired glucose tolerance (IGT) more prevalent in women. To explore whether this sex difference is related to female sex hormones, we performed a cross-sectional analysis of data from 2,164 (1,329 women and 835 men) firstdegree relatives of individuals with type 2 diabetes. Subjects were categorized based on a 75-g oral glucose tolerance test. Sex and hormone replacement therapy (HRT) effects on the distribution of glucose tolerance were assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 41 publications
5
29
1
Order By: Relevance
“…Other studies suggested that the observed gender differences in the glucose metabolism may be mediated by female sex hormones [29]. Estrogen may be influencing fasting glucose levels by impacting insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested that the observed gender differences in the glucose metabolism may be mediated by female sex hormones [29]. Estrogen may be influencing fasting glucose levels by impacting insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The potential reason or reasons for this gender difference in glucose metabolism has not been explored, but some studies suggest that female sex hormones may contribute [26][27][28][29][30], while others failed to see any effect on glucose metabolism [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…4 Postmenopausal women with a family history of T2DM on hormone replacement therapy have an even higher rate of isolated impaired glucose tolerance. 5 Accordingly, postprandial/postload hyperglycemia is more commonly found in females than males and may in part be ascribed to lower height. 6 Recently, a study in healthy, glucose-tolerant subjects showed different gut glucose absorption rates during OGTT in women and men and a negative relationship between body height and gut glucose half-life.…”
Section: Incidence/prevalence and Risk Factorsmentioning
confidence: 99%